The Bishop’s Special Solicitude for a Presbyter Who Has Served Expiatory Penalties for The Delict «Contra Sextum Cum Minore» - Jaszcz, Adam (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
A grave delict contra sextum cum minore committed by a presbyter may result in dismissal from the clerical state. However, in some cases it is possible to impose other expiatory penalties for a determined period. In this case, the offender does not lose the status of a cleric. This means that the incardination may continue, which involves special solicitude on the part of the diocesan bishop, according to c. 384. This paper attempts to examine the nature of this solicitude when the presbyter is the offender of a delict against which the Church has declared a ruthless struggle. Guided by the principle formulated by John Paul II of «zero tolerance», it is necessary consider the capacity of the punished presbyter to carry out pastoral ministry; recognition of his subjective rights, considering the situation in which he finds himself; necessary assistance by taking care of personalized spiritual and intellectual formation. This is an important step towards the creation of a professional system for the protection of minors in the Church.